Stable colony-stimulating factor 1 fusion protein treatment increases hematopoietic stem cell pool and enhances their mobilisation in mice - Simranpreet Kaur; Anuj Sehgal; Andy C. Wu; Susan M. Millard; Lena Batoon; Cheyenne J. Sandrock; Michelle Ferrari-Cestari; Jean-Pierre Levesque; David A. Hume; Liza J. Raggatt; Allison R. Pettit (Journal of Hematology & Oncology, 2021)
Abstract Background Prior chemotherapy and/or underlying morbidity commonly leads to poor mobilisation of hematopoietic stem cells (HSC) for transplantation in cancer patients. Increasing the number of available HSC prior to mobilisation is a potential strategy to overcome this deficiency. Resident bone marrow (BM) macrophages are essential for maintenance of niches that support HSC and enable engraftment in transplant recipients. Here we examined potential of donor treatment with modified recombinant colony-stimulating factor 1 (CSF1) to influence the HSC niche and expand the HSC pool for autologous transplantation. Methods We administered an acute treatment regimen of CSF1 Fc fusion protein (CSF1-Fc, daily injection for 4 consecutive days) to naive C57Bl/6 mice. Treatment impacts on macrophage and HSC number, HSC function and overall hematopoiesis were assessed at both the predicted peak drug action and during post-treatment recovery. A serial treatment strategy using CSF1-Fc followed by granulocyte colony-stimulating factor (G-CSF) was used to interrogate HSC mobilisation impacts. Outcomes were assessed by in situ imaging and ex vivo standard and imaging flow cytometry with functional validation by colony formation and competitive transplantation assay. Results CSF1-Fc treatment caused a transient expansion of monocyte-macrophage cells within BM and spleen at the expense of BM B lymphopoiesis and hematopoietic stem and progenitor cell (HSPC) homeostasis. During the recovery phase after cessation of CSF1-Fc treatment, normalisation of hematopoiesis was accompanied by an increase in the total available HSPC pool. Multiple approaches confirmed that CD48−CD150+ HSC do not express the CSF1 receptor, ruling out direct action of CSF1-Fc on these cells. In the spleen, increased HSC was associated with expression of the BM HSC niche macrophage marker CD169 in red pulp macrophages, suggesting elevated spleen engraftment with CD48−CD150+ HSC was secondary to CSF1-Fc macrophage impacts. Competitive transplant assays demonstrated that pre-treatment of donors with CSF1-Fc increased the number and reconstitution potential of HSPC in blood following a HSC mobilising regimen of G-CSF treatment. Conclusion These results indicate that CSF1-Fc conditioning could represent a therapeutic strategy to overcome poor HSC mobilisation and subsequently improve HSC transplantation outcomes.